Nurses professional identity issues - Bēta, Gunta (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Researches and publications on the professional identity of nurses and on the factors shaping it are comparatively rare in Latvia. In this respect, of significance is the entirety of several factors in projections of the personality of an individual and of assessment, provided by the patients and society: values, attitude and knowledge. The scope of the article applies to three periods in the life of a nurse: period till acquirement of professional education and periods of professional education and professional activities, during which forms the value system of the prospective nurse and develops her / his professional socialisation that in general encourages formation of the professional identity of a nurse.